IMPLEMENTASI KONTROLER FUZZY PADA MOTOR DC RS-775 SEBAGAI MESIN PENGUPAS BAWANG DENGAN METODE SUGENO - Salman Farisi; Bambang Siswojo; Tri Nurwati (Jurnal Mahasiswa TEUB, 2021)
AbstrakBidang kontrol adalah hal yang vital dalam sektor industri di dunia saat ini, khususnya dalam industri makanan. Motor DC (Direct Current) adalah plant yang paling sering digunakan dalam perkembangan dunia teknologi kontrol. Pada umumnya Motor DC memiliki Respon yang sangat cepat namun masih memiliki nilai error yang cukup besar. Dengan adanya perkembangan teknologi berhasil dikembangkan salah satu controller seperti FLC (Fuzzy Logic Control) dapat dibangun sebuah controller yang sangat adaptif dalam perubahan input sistem. Logika Fuzzy adalah suatu cara yang tepat untuk memetakan suatu ruang input ke dalam ruang output. Dalam penelitian ini untuk membangun sebuah FLC (Fuzzy Logic Control) digunakan sebuah metode yaitu Sugeno.Kata kunci – motor DC RS-775, kontrol kecepatan, kontrol fuzzyAbstractIn this research, we made a system for controlling the speed of DC RS-775 as a motor in a shallot peeler and slicer machine by using Fuzzy logic controller. The goal of this research is designing the control system of DC RS-775 by using the fuzzy logic controller to able to reach the setpoint and able to resist the disturbances. This research uses the Fuzzy logic method to take a conclusion. This research with Sugeno method uses 2 inputs which are error and delta error. The errors and delta errors are represented by Negative Big (NB), Negative Small (NS), Zero (0), Positive Small (PS), Positive Big (PB). The output of this method is changing the variable of PWM on DC RS-775 which is represented by Negative Big (NB), Negative Small (NS), Zero (0), Positive Small (PS), Positive Big (PB). The result of this research is the natural response of DC RS-775 generates ts at 5.5s. The response of DC motor after controlled by fuzzy logic controller with setpoint variable of 5000 rpm, generates 1.9% error steady state and ts at 1.2s. On testing of changing variable input every 10s Fuzzy controller ables to control the speed of DC RS-775 to reach the setpoint. When it was tested with disturbances, DC RS-775 able to keep the steady state at 5000 rpm with 1.5% error steady state, ts at 1.4s, and variable of Mp 3.27%.Key Word: motor DC RS-775, speed control, Fuzzy logic controller.